A Radical Re-evaluation of Landscape Stewardship and Conservation Planning Priorities - Michael Peter Amato (Fábos Conference on Landscape and Greenway Planning, 2025)
Landscape conservation is at an inflection point. Massive acreages of land held by baby boomers will change hands in the next several decades. To meet climate mitigation goals, landscape conservation needs an unfathomable amount of funding and manpower to conserve as much ‘ecologically valuable’ land as possible. At this crucial time, the theories that support and direct landscape conservation are as important as the work itself. The purpose of this paper is to examine several of the theories that inform conservation planning through a critical lens. There are several problematic topics of discussion that are directly related to this issue worthy of examination such as: environmental justice, the housing crisis, the land back movement, the myth of the pristine, and allocation of funds towards invasive plant removal programs. This paper will make the argument for a re-evaluation of conservation planning theory and priorities in New England based on recent research and emerging knowledge.
Keywords: Regional Planning; Landscape Conservation; Invasive Plants; Environmental Justice